Automotive Brake Friction Part Recovery Technology Using Composite Materials - Haydaraliyev Ulugbek G‘ayrat o‘g‘li; Jamshed Sadulloevich Avliyokulov; Khurshidbek Ikromovich Nurmetov (Zien Journals, 2021)
The composition will consist of at least two components among the materials. There are composite materials - for example, there are plywood. In all other composites, the components can be divided into a matrix or a connector, and electrical energy - to fill. Composites are usually distinguished by the type of reinforcing filler or the substance of the Matrix.
Keywords: Components can be divided; vacuum infusion; matrix or a connector; components